The effect of AGN feedback on Sunyaev-Zeldovich properties of simulated galaxy clusters. Issue Volume 12:Issue S324(2016) (23rd June 2017) - Fabjan, Dunja; Planelles, S.; Borgani, S.; Murante, G.; Rasia, E.; Biffi, V.; Truong, N.; Ragone-Figueroa, C.; Granato, G. L.; Dolag, K.; Pierpaoli, E.; Beck, A. M.; et al.
Abstract: We studied the imprints that feedback from Active Galactic Nuclei (AGN) leaves on the intracluster plasma during the assembly history of galaxy clusters. To this purpose we used state-of-the-art cosmological hydrodynamical simulations based on an updated version of the Tree-PM SPH GADGET-3 code, comparing three sets of simulations with different prescriptions for the physics of baryons (including AGN and/or stellar feedback). We explore the effect of these different physics, in particular AGN feedback, on IntraCluster medium (ICM) properties observed via Sunyaev-Zel'dovich (SZ) effect using an extended set of galaxy clusters (~100 clusters with M 500 masses above 5 × 10 13 M ⊙ /h). Some of the main findings are that the scaling relation between the integrated SZ flux and the galaxy cluster total mass is in good accordance with several observed samples, especially for massive clusters, and does not show any clear redshift evolution, with the slope of the relation close to the theoretical one in the AGN feedback case. As for the scatter of this relation, we obtain a mild dependence on the cluster dynamical state.